Psychometric properties of the Persian version of the students' conceptions of assessment: SCoA inventory in medical university in Iran - Maryam Akbarilakeh; Shiva Kazemy; Soleiman Ahmady; Azizollah Arbabisarjou (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Student assessment is one of the main parts of educational planning, and improves the quality of education. Students understanding and feeling about assessment might affect significantly on learning and academic achievement. Considering the importance of this issue, and the lack of a valid and reliable Persian tool in medical universities for measuring this concept to measure students' perceptions and understandings of assessment, the current study aim was to determine the psychometric properties of (Students' Conceptions of Assessment - SCoA) inventory during the basic sciences students in medicine, dentistry, pharmacy in Kermanshah University of Medical Sciences. METHODS AND MATERIALS: This is a cross-sectional study design. In order to carry out this study, SCoA inventory was translated and culturally adopted. To measure validity, reliability, and normalize the inventory, it was distributed among the study population composed of 302 students of Kermanshah University of Medical Sciences during the academic year 1400-1401 who met the inclusion criteria. The collected data were analyzed by confirmatory factor analysis (CFA) and Cronbach's alpha using SPSS version 23 and Amos software. RESULTS: The results of data analysis showed that of the 302 participants, 119 were men and 183 were women. The mean age of students was 21.69 ± 2.16 years. Content validity was calculated, and it was reported 0.88. Cronbach's alpha was used to determine the internal consistency, and its value was 0.775. The construct validity of SCoA inventory was assessed using CFA by EQS version 6.1. The value of root mean square error of approximation (RMSEA) was 0.092 with a 98% confidence interval, and the Goodness of fit index (GFI) value was 0.99. CFA for all items loaded across four factors, and this four-factor inventory showed a good fit in the Iranian community. CONCLUSION: For the first time, the psychometric test of SCoA inventory has been carried out at Kermanshah University of Medical Sciences. The Persian version of this inventory has good validity and reliability in Iran and is a useful tool for measuring the SCoA in medical university. Researchers and those interested in medical education and development centers can benefit from the results of this study. Also, this inventory has been applicable to determine the attitude and perceptions of students about assessment.